(untitled) (Journal of the College of Basic Education, 2022)
The spark gap is simply a high voltage , high speed switch for firing the laser,there are a number of applications in both civilian and military markets where CO2 lasers can be used to advantage over other coherent light source .In all of the following applications the laser is used in a pulsed mode and the influence of triggered spark gap has been found to be a most useful device for achieving this operation . The two - electrode spark gap is designed to drive pulse laser and transmission mode systems by means of switching high voltage up to 30 KV at a repetition rate as high as 100 Hz . The device has been operated for several months , firing in a variety of applications without any electrode failure